2019
DOI: 10.1159/000502133
|View full text |Cite
|
Sign up to set email alerts
|

Etomidate Modulates the Tactile Stimulation-Evoked Field Potential Responses in Cerebellar Granule Cell Layer in vivo in Mice

Abstract: Etomidate (ET) produces sedation by binding on the γ-aminobutyric acid type A (GABAA) receptors. We previously found that ET inhibited cerebellar Purkinje cells activity via both GABAA and glycine receptors in vivo in mice, suggesting that ET modulated sensory information synaptic transmission in cerebellar cortex. In this study, we investigated the effect of ET on the sensory stimulation-evoked responses in the cerebellar granule layer (GL) in urethane-anesthetized mice, using electrophysiological and pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…It has been reported that etomidate reduced glutamate uptake in rat-cultured glial cells through PKA signaling pathway [31]. Consistent with our previous study [24], etomidateinduced depression of the sensory stimulation-evoked excitatory component in the cerebellar GL through PKA signaling pathway in the absence of GABA A and glycine receptors activity. The present results suggest that etomidate couples to CB1 receptor that induces a depression of adenylyl cyclase-cyclic AMP signal transduction, which might lead to downregulation of proteins phosphorylation on synaptic vesicles in CF-Purkinje cell synapses, resulting in a decrease in glutamate release from CF onto Purkinje cells.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…It has been reported that etomidate reduced glutamate uptake in rat-cultured glial cells through PKA signaling pathway [31]. Consistent with our previous study [24], etomidateinduced depression of the sensory stimulation-evoked excitatory component in the cerebellar GL through PKA signaling pathway in the absence of GABA A and glycine receptors activity. The present results suggest that etomidate couples to CB1 receptor that induces a depression of adenylyl cyclase-cyclic AMP signal transduction, which might lead to downregulation of proteins phosphorylation on synaptic vesicles in CF-Purkinje cell synapses, resulting in a decrease in glutamate release from CF onto Purkinje cells.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies demonstrate that activation of CB1 receptor by etomidate depresses neuronal activity in hippocampus and basolateral amygdale [18] and inhibits the facial stimulation-evoked mossy fiber-granule cell synaptic transmission in mouse cerebellar cortex [24]. Therefore, we used a selective CB1 receptor antagonist, AM-251 (5 μmol/L), to determine whether etomidate-induced inhibition of spontaneous CSs activity of Purkinje cells via activation of CB1 receptor in the absence of GABA A and glycine receptors activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations